1D to 3D dimensional crossover in the superconducting transition of the quasi-one-dimensional carbide superconductor Sc3CoC4. (3rd February 2015) - He, Mingquan; Wong, Chi Ho; Shi, Dian; Tse, Pok Lam; Scheidt, Ernst-Wilhelm; Eickerling, Georg; Scherer, Wolfgang; Sheng, Ping; Lortz, Rolf
Abstract: The transition metal carbide superconductor Sc3 CoC4 may represent a new benchmark system of quasi-one-dimensional (quasi-1D) superconducting behavior. We investigate the superconducting transition of a high-quality single crystalline sample by electrical transport experiments. Our data show that the superconductor goes through a complex dimensional crossover below the onset T c of 4.5 K. First, a quasi-1D fluctuating superconducting state with finite resistance forms in the [CoC4 ]∞ ribbons which are embedded in a Sc matrix in this material. At lower temperature, the transversal Josephson or proximity coupling of neighboring ribbons establishes a 3D bulk superconducting state. This dimensional crossover is very similar to Tl2 Mo6 Se6, which for a long time has been regarded as the most appropriate model system of a quasi-1D superconductor. Sc3 CoC4 appears to be even more in the 1D limit than Tl2 Mo6 Se6 .